2019
DOI: 10.1007/jhep11(2019)041
|View full text |Cite
|
Sign up to set email alerts
|

Uniqueness of Galilean conformal electrodynamics and its dynamical structure

Abstract: We investigate the existence of action for both the electric and magnetic sectors of Galilean Electrodynamics using Helmholtz conditions. We prove the existence of unique action in magnetic limit with the addition of a scalar field in the system. The check also implies the non existence of action in the electric sector of Galilean electrodynamics. Dirac constraint analysis of the theory reveals that there are no local degrees of freedom in the system. Further, the theory enjoys a reduced but an infinite dimens… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(29 citation statements)
references
References 44 publications
0
29
0
Order By: Relevance
“…• Magnetic sector: It is clear from our discussions that the Magnetic sector of Carrollian electrodynamics and scalar electrodynamics cannot have an action formulation without the inclusion of extra fields. In [26], the magnetic sector was analysed from the point of view of Helmholz conditions and it was found that the addition of an extra scalar or an extra vector does not help. We would like to find the minimal set of extra fields required to formulate an action principle for this theory.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…• Magnetic sector: It is clear from our discussions that the Magnetic sector of Carrollian electrodynamics and scalar electrodynamics cannot have an action formulation without the inclusion of extra fields. In [26], the magnetic sector was analysed from the point of view of Helmholz conditions and it was found that the addition of an extra scalar or an extra vector does not help. We would like to find the minimal set of extra fields required to formulate an action principle for this theory.…”
Section: Discussionmentioning
confidence: 99%
“…The necessary and sufficient conditions to determine the "inverse" problem of calculus of variation is given by the Helmholtz conditions [28][29][30]. In [26], the Helmholtz conditions were used for determining uniquely an action for the equations of motion of the magnetic sector of Galilean electrodynamics and violated for the corresponding magnetic sector.…”
Section: Helmholtz Conditions For Carrollian Scalar Edmentioning
confidence: 99%
See 1 more Smart Citation
“…The theory (2.11) does not possess propagating degrees of freedom. This can be seen by exploring the structure of the poles in the gauge field propagator, or alternatively by a Dirac constraint analysis, see, e.g., [47]. 12 To introduce some propagating degrees of freedom, we couple the GED theory to a Schrödinger scalar field σ.…”
Section: Jhep10(2020)195mentioning
confidence: 99%
“…At leading order in α and in the flat closed string background, the DBI action in (4.6) gives rise to Galilean Electrodynamics (GED). GED is a non-dynamical U(1) gauge theory that is invariant under a Galilean boost transformation, and has been studied at the classical level in [18][19][20]36]. In [37], the one-loop beta-functions of Galilean electrodynamics coupled to a Schrödinger scalar in 2 + 1 dimensions are computed, where the renormalization of the dynamical Schrödinger scalar receives highly nontrivial contributions from interactions with the non-dynamical gauge sector.…”
Section: Galilean Electrodynamics On a Newton-cartan Backgroundmentioning
confidence: 99%